Group 2 innate lymphoid cells are key in lipid transfer protein allergy pathogenesis - Palomares, Francisca; Pérez-Sánchez, Natalia; Nieto, Nazaret; Núñez, Rafael; Cañas, José Antonio; Martín-Astorga, María del Carmen; Cruz-Amaya, Anyith; Torres, María José; Eguíluz-Gracia, Ibon; Mayorga, Cristobalina; Gómez, Francisca (Frontiers in Immunology, 2024)
Background: Immunopathology in food allergy is characterised by an uncontrolled type 2 immune response and specific-IgE production. Recent studies have determined that group 2 innate lymphoid cells (ILC2) participate in the food allergy pathogenic mechanism and their severity. Our objective was to investigate the role of ILC2 in peach-allergic patients due to non-specific lipid transfers proteins (Pru p 3) sensitisation. Methods: The immune response in peripheral blood mononuclear cells was characterised in lipid transfer protein-allergic patients and healthy controls. We have analysed the Pru p 3 uptake on ILC2, the expression of costimulatory molecules and their involvement on the T-cell proliferative response and cytokine production under different experimental conditions: cytokines involved in group 2 innate lymphoid cells activation (IL-33 and IL-25), Pru p 3 as main food allergen and the combination of both components (IL-33/IL-25+Pru p 3) using cell sorting, EliSpot, flow cytometry, and confocal microscopy. Results: Ours results show that Pru p 3 allergen is uptaken by group 2 innate lymphoid cells regulating their costimulatory molecules expression (CD83 and HLA-DR) depending on the presence of Pru p 3 and its combination with IL-33/IL-25. The Pru p 3-stimulated-ILC2 induce specific GATA3+Th2 proliferation and cytokine (IL-4, IL-5 and IL-13) production in lipid transfer protein-allergic patients in a cell contact-dependent manner with no changes in Tbet+Th1- and FOXP3+Treg-cell differentiation. Conclusion: The results indicate that in lipid transfer protein-allergic patients, the responsible allergen, Pru p 3, interacts with group 2 innate lymphoid cells promoting a Th2-cell response. Our results might be of interest in vivo, as they show a role of group 2 innate lymphoid cells as antigen presenting cell, contributing to the development of food allergy. Consequently, group 2 innate lymphoid cells may be considered as potential therapeutic targets.